2013
DOI: 10.1056/nejmoa1214854
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir for Hepatitis C Genotype 2 or 3 in Patients without Treatment Options

Abstract: In patients with HCV genotype 2 or 3 infection for whom treatment with peginterferon and ribavirin was not an option, 12 or 16 weeks of treatment with sofosbuvir and ribavirin was effective. Efficacy was increased among patients with HCV genotype 2 infection and those without cirrhosis. In previously treated patients with genotype 3 infection, 16 weeks of therapy was significantly more effective than 12 weeks. (Funded by Gilead Sciences; POSITRON and FUSION ClinicalTrials.gov numbers, NCT01542788 and NCT016048… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
960
5
27

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 995 publications
(1,035 citation statements)
references
References 13 publications
43
960
5
27
Order By: Relevance
“…19 In the POSITRON trial, SVR rate was 93% (101/109) among IFN-unwilling, ineligible, or intolerant GT-2 patients. 35 In the FUSION trial, among treatment-experienced GT-2 patients, SVR rates were better, with 16 weeks of therapy (94%) than after 12 weeks (86%). This was also the case in GT-2 patients with cirrhosis; SVR rates were better after 16 weeks of therapy (78%; 7/9) than after 12 weeks (60%; 6/10).…”
Section: Genotypesmentioning
confidence: 98%
See 2 more Smart Citations
“…19 In the POSITRON trial, SVR rate was 93% (101/109) among IFN-unwilling, ineligible, or intolerant GT-2 patients. 35 In the FUSION trial, among treatment-experienced GT-2 patients, SVR rates were better, with 16 weeks of therapy (94%) than after 12 weeks (86%). This was also the case in GT-2 patients with cirrhosis; SVR rates were better after 16 weeks of therapy (78%; 7/9) than after 12 weeks (60%; 6/10).…”
Section: Genotypesmentioning
confidence: 98%
“…This observation indicated that cirrhotic patients might need therapy for more than 12 weeks. 35 In the VALENCE trial, among patients with GT-2 HCV treated for 12 weeks with SOF and RBV, SVR rate was 93% (68/73), being 94% (59/63) without and 82% (9/11) with cirrhosis. According to treatment experience, SVR rate was 97% (29/30) in treatment-naive noncirrhotic patients, 100% (2/2) in treatment-naive cirrhotic patients, 91% (30/33) in treatment-experienced noncirrhotic patients, and 88% (7/8) in treatment-experienced cirrhotic patients.…”
Section: Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Total costs of HCV medication guidelines by the American Association for the Study of Liver Diseases (AASLD) and Infectious Diseases Society of America (IDSA) as of January 2015 with cure rates from clinical trials is summarized in Table 1. 28,29,44,31,32,45 For the purposes of calculating total medication costs, we assumed entirely interferon-free regimens with the highest SVRs from clinical trials across all genotypes, given the current community standard of care. For genotypes 1 and 4, we calculated total drug costs of a SOF/LDV regimen, with varying duration of 8 to 24 weeks based on fibrosis and treatment history for genotype 1 patients.…”
Section: Methodsmentioning
confidence: 99%
“…SVRs as high as 97 % were achieved in genotype 2 patients with SOF+RBV combination therapy. 28,29 In the fall of 2014, SOF and ledipasvir (LDV) together were approved as a fixed-dosed combination and SOF+SMV were approved as combination therapy. More recently, the FDA has approved the co-formulated ombitasvir, paritaprevir, and ritonavir with dasabuvir regimen (OBV/PTV/r+DSV) for genotype 1 patients and those with advanced cirrhosis, also eliminating RBV in some cases.…”
Section: Introductionmentioning
confidence: 99%